2019
DOI: 10.1108/medar-11-2018-0406
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain and its implications for accounting and auditing

Abstract: Purpose Technological developments such as blockchain seem to be the next step in a digital era and might reshape the way we do business. They are expected to have an impact on both business and society in the next few decades. This paper aims to provide general insights into blockchain technology and the extent to which it might transform the accounting system. Design/methodology/approach Analysing the previous literature, the paper provides a general overview of this phenomenon, identifying pending technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(214 citation statements)
references
References 23 publications
2
164
0
8
Order By: Relevance
“…However, subsequent observations, often on the potentially disruptive nature of blockchain technology or the challenges relating to implementation, continued to make the same claims. For instance, Bonsón and Bednárová (2019: 725) identify “the pending challenges for blockchain, such as scalability, flexibility, a suitable architecture, and cybersecurity,” especially relating to integrating blockchain with existing accounting systems. Similarly, Fuller and Markelevich (2020: 34) analyze “data security, privacy, and implementation considerations,” especially as they relate to accounting information systems.…”
Section: Resultsmentioning
confidence: 99%
“…However, subsequent observations, often on the potentially disruptive nature of blockchain technology or the challenges relating to implementation, continued to make the same claims. For instance, Bonsón and Bednárová (2019: 725) identify “the pending challenges for blockchain, such as scalability, flexibility, a suitable architecture, and cybersecurity,” especially relating to integrating blockchain with existing accounting systems. Similarly, Fuller and Markelevich (2020: 34) analyze “data security, privacy, and implementation considerations,” especially as they relate to accounting information systems.…”
Section: Resultsmentioning
confidence: 99%
“…Such mixed views echo recent discussions in studies (such as Cao et al 2019), who argue that modern auditing standards do not provide sufficient opportunity for BDA to be fully exploited in the conduct of an audit, and these authors specifically argue for the revision of a number of international auditing standards. The reality is that technology seems to be advancing rapidly, and new consortiums have emerged to accelerate the definition of industrial standards and to foster collaboration (Bonson and Bednarova 2019). Regulators may need to find ways to monitor how the ability to record transactions in real time affects the accounting and auditing processes, and how it alters the nature of accountants' and auditors' tasks.…”
Section: Financial and Audit Market Regulators: The Need To Respond Tmentioning
confidence: 99%
“…Our findings are consistent with a statement made in a recent Australian report by Davern et al (2019) that indicated that while blockchain will make inroads into some very specific application areas its impact on the value-adding activities of accounting professionals has likely been over-hyped. Also, another recent study by Bonson and Bednarova (2019) identified the pending challenges for blockchain, such as scalability, flexibility, a suitable architecture and cybersecurity. In addition, it highlighted the need to integrate blockchain technology fully into a real accounting ecosystem, with a consensus needed between regulators, auditors and other parties.…”
Section: Summary and Limitationsmentioning
confidence: 99%
“…The only source of accounting data is guaranteed, and the accounting data cannot be falsified [86] The only source of auditing data is guaranteed, and the audit data cannot be falsified [87] Distributed ledger (Decentralized) [80] Enhance transaction transparency Improvement in the transparency of accounting information [81] Improvement in the authenticity and reliability of audit data [82] Timestamp [83] Clear transaction order Improvement in the difficulty of changing data and retain permanent accounting records [80] Improvement in the reliability and timeliness of audit data, and lay a solid foundation for continuous audit and real-time audit [84] Network consensus [85] Verify transaction legality Improvement in accounting efficiency; provision of real-time transaction clearing or settlement [88] Improvement in the authenticity, reliability and timeliness of audit data, and lay a solid foundation for continuous audit and real-time audit [89] Programmable [90] None…”
Section: A Blockchain Technologymentioning
confidence: 99%
“…On the other hand, the consensus mechanism for blockchain enables all data to be jointly confirmed the first time, which can guarantee the timeliness and accuracy of the data. Greatly improving the authenticity and integrity of the data saves many inquiry and correspondence procedures, thereby improving the efficiency of audit work and saving labour costs [89]. e. The programmable feature enables auditors to write audit algorithms and audit business processing rules according to different audit application scenarios, laying a solid foundation for the automation of audit work [90].…”
Section: A Blockchain Technologymentioning
confidence: 99%